Transform‐based watermarking algorithm maintaining perceptual transparency. Issue 5 (1st May 2018) - Shahdoosti, Hamid Reza; Salehi, Mohammad
Abstract : Here, a novel, yet simple, transform‐based watermarking scheme for copyright protection has been proposed. The proposed method takes advantage of the rotation invariant property of the ripplet‐II transform which makes the proposed method robust against rotation attacks. In the proposed method, firstly a cost function of perceptual transparency is formed in the ripplet‐II domain. Secondly, the ridge regularisation constraint is added to the cost function to avoid the singularity problem in the model. In order to obtain the embedding weights, this function is minimised. Therefore, the embedding weights are adaptive to both the host image and watermark. Simulation results demonstrate that the proposed algorithm not only provides an excellent watermark invisibility, but it also shows superior robustness against common image processing operations and acceptable robustness against geometric distortions.